THE ANALYSIS OF STRUCTURE SHIFT IN THE ENGLISH TRANSLATION OF THESIS ABSTRACTS FOUND AT TEACHER TRAINING AND EDUCATION FACULTY HALU OLEO UNIVERSITY - Supriyatno, Iwan (Journal of Teaching of English, 2019)
This study is an attempt to contribute in the study of translation shift. The goal is to  find  out  and  describe  the  structure  shift  that  occurs in  Indonesian-English translation.  This  study also  analized  the  accuracy of  translations  that  contain structure shifts. The analysis was specifically directed to the thesis abstracts and their English translation version that taken from the library of Teacher Training and Education Faculty,  Halu Oleo University. This study employed qualitative design. The total abstracts involved as source of data in this study were 2 abstracts that  came  from  one  study  program,  that  is,  Early-childhood  Education.  The analysis of the structure shift was based on the theory of Catford (1965). The result revealed that the structure shifts do exist in the translation of the thesis abstracts.   Specifically,   there   are   10   structure   shifts   found   in   this   study. Furthermore from these data, 4 of them are considered inaccurate translation; 5 are considered accurate translation; and only 1 is considered very accurate translation. This study concluded that the translator‟s comprehension about the target  language  system  is  highly  required  in  order  to  produce  an  accurate translation. This study also suggests that the translation shifts shoud be included as one topic to be discussed in translation class. Keywords: Structure shift, Accuracy, Thesis Abstract